Novel TTG1 Mutants Modify Root-Hair Pattern Formation in Arabidopsis - Long, Yun; Schiefelbein, John (Frontiers in Plant Science, 2020)
The patterning of root-hair and non-hair epidermal cells in the Arabidopsis root is governed by a network of transcriptional regulators. The central MYB-bHLH-WD40 (MBW) transcriptional complex includes the WD40-repeat protein TRANSPARENT TESTA GLABRA1 (TTG1). To clarify the role of TTG1, we describe the identification and analysis of two new ttg1 mutants. Each of these mutants contains a single nucleotide change in the TTG1 gene, which causes a single amino-acid substitution in the predicted TTG1 protein and alters root-hair pattern formation. Surprisingly, these new ttg1 mutants exhibit decreased root-hair formation, particularly in the caprice (cpc) mutant background, rather than increased root-hair formation as reported for strong ttg1 mutants. We show that the unique phenotype of these mutants is due to differential effects of the altered TTG1 proteins on target gene expression, associated with a weakened ability to interact with its GLABRA3 bHLH partner. These findings demonstrate the crucial role of TTG1 for the appropriate balance of target gene activation to achieve the proper pattern of epidermal cell types during Arabidopsis root development.